A STUDY ON MIGRATORY POPULATION IN INDIA: SOME SELECTED STATES - Chakravarty, Anjan (International Journal of Research -GRANTHAALAYAH, 2020)
India is the motherland of diverse culture, beliefs and traditions. Indians have lived through ages with the maxim “Unity in Diversity”. In this so varied nature of population, migrations intra-state and inter-state, as well as, international from bordering countries have affected the characteristics of the inhabitants. In this study, we are aiming to assess the nature of population India has, both in rural and urban categories and how these two categories of population are correlated with each other and try to analyze factors which create an impact on the character of the population. We have selected four states, namely, Gujarat, Maharashtra, Bihar and West Bengal for the purpose of our learning.